2014
DOI: 10.1177/0040517514521115
|View full text |Cite
|
Sign up to set email alerts
|

Thermal energy transfer through heat protective clothing during a flame engulfment test

Abstract: The flame engulfment test according to ISO 13506 assesses the protective performance of ready-made heat and flame protective clothing when exposed to a flash fire condition using an instrumented manikin. It uses a thermal model of the human skin to predict the risk of skin burns. This evaluation method is based on a pass/fail criterion, as either a burn is predicted or not. Therefore, it provides only limited information about the transfer of heat through the protective clothing. In this study, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…12 In the most used models, the thermal properties of skin are supposed to remain constant during temperature rises. 13 Both ASTM F1930 and ISO 13506-2 provide further information on the thermal conductivity of each of the layers which varies with temperature due to the generalized thermo-physical characteristics of the layer components. However, the developed relationships were based on limited experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In the most used models, the thermal properties of skin are supposed to remain constant during temperature rises. 13 Both ASTM F1930 and ISO 13506-2 provide further information on the thermal conductivity of each of the layers which varies with temperature due to the generalized thermo-physical characteristics of the layer components. However, the developed relationships were based on limited experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the penetration of the radiation is limited, and it is assumed that heat conduction is the only mode of heat transfer in the skin and subcutaneous layers (adipose) . In the most used models, the thermal properties of skin are supposed to remain constant during temperature rises . Both ASTM F1930 and ISO 13506‐2 provide further information on the thermal conductivity of each of the layers which varies with temperature due to the generalized thermo‐physical characteristics of the layer components.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional burn prediction methods are pass/fail criteria. This suggests that the method only indicates whether the burn degree is reached or not, without showing whether the energy transferred just induced the burn or whether it was far higher than the burn threshold [14]. An interlaboratory trial provided evidence of no uniform ranking of the institutes concerning the predicted burn area [7].…”
Section: 2mentioning
confidence: 99%
“…An interlaboratory trial provided evidence of no uniform ranking of the institutes concerning the predicted burn area [7]. Rossi have suggested that the total transferred energy be used; however, it is based on physical values instead of skin burn information [14]. Thus, better prediction methods are needed, with high repeatability and low coefficients of variation and at the same time indicating enough information of the potential skin burn risk.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation